Leadership Styles and Educational Organization Performance - Lilly Linne A. Kainde; Novie P. Sibilang (Economics and Digital Business Review, 2024)
This research aims to analyze the influence of leadership styles on school organizational performance. The research population comprises all accredited Adventist High Schools (SMA) in Indonesia by the National Accreditation Board (BAN) and the Adventist Accrediting Association (AAA). There were 408 respondents in this study, consisting of both permanent and honorary teachers from 24 schools accredited by BAN and AAA for high schools in Indonesia. This research employed purposive sampling method for sample selection and data collection through survey method. This research employs confirmatory analysis, which allows researchers to assess the extent to which the measured variables (constructs) reflect the concepts they are supposed to measure. Using Structural Equation Modeling (SEM) analysis at the structural level, this research revealed a substantial influence of leadership styles on organizational performance. Specifically, transactional leadership style has a significant positive influence on school organizational performance, while transformational leadership style has a significant negative influence on school organizational performance. The implications of this research, viewed within the context of educational organizations that emphasize operational standards fulfillment, suggest that schools should provide employees the freedom to work consistently and focus on achieving short-term goals, led by the school principal with a transactional leadership style. Subsequent studies are expected to conduct empirical testing within government-owned schools.